2013
DOI: 10.1111/aos.12107
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile eye growth, when completed? An evaluation based on IOL‐Master axial length data, cross‐sectional and longitudinal

Abstract: . Purpose:  To test Sorsby’s classical statement of axial eye growth as completed at the age of 13 years, with a view also to differentiating between basic eye growth and juvenile elongation associated with eventual refractive change towards myopia. Methods:  (i) A total of 160 healthy eyes close to emmetropia were included in a cross‐sectional set‐up (age 4–20 years, 91 males, 69 females), and (ii) 78 longitudinal data sets (67 male and 11 female annual repeat exams over 2–7 years, n = 30; age span 4–19 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 16 publications
6
45
1
Order By: Relevance
“…17 This is also supported by recent report from 160 young Danish emmetropes, which described comparable median annual change in axial length of 0.23 mm, 0.15 mm, 0.09 mm, and 0.08 mm within the 5.0 to 7.9 years, 8.0 to 10.0 years, 11.0 to 13.9 years, and 14.0 to 15.9 years age groups, respectively. 27 In the OSLM, change in ACD was comparable to that of the NICER Study with continual deepening of the anterior chamber that slowed after 10 to 11 years among all refractive error groups. 2 Interestingly, within the SCORM, an increase in ACD was observed among younger children with a subsequent decrease in depth of the anterior chamber at approximately 10 years of age, resulting in inverted U-shaped growth curves.…”
Section: Discussionmentioning
confidence: 56%
“…17 This is also supported by recent report from 160 young Danish emmetropes, which described comparable median annual change in axial length of 0.23 mm, 0.15 mm, 0.09 mm, and 0.08 mm within the 5.0 to 7.9 years, 8.0 to 10.0 years, 11.0 to 13.9 years, and 14.0 to 15.9 years age groups, respectively. 27 In the OSLM, change in ACD was comparable to that of the NICER Study with continual deepening of the anterior chamber that slowed after 10 to 11 years among all refractive error groups. 2 Interestingly, within the SCORM, an increase in ACD was observed among younger children with a subsequent decrease in depth of the anterior chamber at approximately 10 years of age, resulting in inverted U-shaped growth curves.…”
Section: Discussionmentioning
confidence: 56%
“…The increase in mean vessel calibers is in line with continued slow growth of the globe from the age of 13 to adulthood. 25,26 Progressive venular vasodilation was greatest in adolescents with higher baseline HbA1c and longer duration of diabetes. This likely represents the adverse effects of hyperglycemia on endothelial function, by impairing the ability of retinal vessels to autoregulate.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence of this late ocular growth is that 40% of some retrospectively studied adult cohorts were prescribed glasses for distance vision when aged 20-35 [47,48]. Adult onset myopia has been also associated with axial elongation [49][50][51] and a recent small prospective study has shown that although normal ocular growth in emmetropes may end by age 10-13 as was originally proposed by Sorsby, there is evidence of further slow ocular growth in later years [52]. In East and South East Asia, where 80% of children in the younger generations have myopia by age 18 [33], adult onset myopia is not likely to be an issue, as most subjects are already myopic by the end of the school years.…”
Section: The Changing Natural History Of Myopia Developmentmentioning
confidence: 99%